Comparing the effects of education through compact disk and social media on knowledge and practice regarding the assessment of preterm infant behavior among nurses in neonatal intensive care units - Leila Valizadeh; Mohammad Asghari Jaffar Abadi; Parvaneh Agha Jari; Parstoo Jalili (Kashan University of Medical Sciences, 2021)
Background: Nurses in neonatal intensive care units (NICUs) need adequate professional knowledge and skills for providing quality developmental care to premature newborns. Objectives: This study aimed to compare the effects of education through compact disk (CD) and social media (SM) on knowledge and practice regarding the assessment of preterm infant behavior (APIB) among nurses in NICUs. Methods: This quasi-experimental study was conducted on fifty NICU nurses. They were randomly allocated to a CD and a SM group. The intervention for both the groups was the same and consisted of education about APIB. Participants' APIB-related knowledge and practice were assessed before and after the intervention using a researcher-made knowledge questionnaire and the APIB checklist, respectively. Data were analyzed through the Chi-square, the independent-samples t, and the paired-samples t-tests as well as the analysis of covariance. Results: The pretest mean scores of knowledge and practice were, respectively, 9.72 ± 4.95 and 207.64 ± 109.49 in the SM group and 9.16 ± 5.94 and 209.88 ± 110.46 in the CD group. After the study intervention, these values significantly increased to 14.80 ± 1.80 and 361.96 ± 38.24 in the SM group (P < 0.05) and 12.46 ± 2.10 and 295.44 ± 53.30 in the CD group (P < 0.05). Although there were no significant differences between the groups regarding the pretest mean scores of knowledge and practice (P > 0.05), the posttest mean scores of knowledge and practice in the SM group were significantly greater than the CD group (P < 0.05). Conclusion: SM-based education is more effective than CD-based education in improving APIB-related knowledge and practice among NICU nurses.